TYPES OF PRONOUNCIATION IN THE LANGUAGE - Abdupattayeva Gulshodaxon Jaloliddin qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: The accent that is historically considered as the most respectable and standard type of spoken British English is called Received Pronunciation (RP). This article entails the definition of RP, whether it is geographically neutral, the number of speakers, whether sub-varieties exist, how appropriate a choice it is as a standard, and how the accent has altered over time. In addition, the study of RP focuses solely on issues of pronunciation; vocabulary, grammar, and style, which are important to the study of language standards, are not taken into account.